Broadband radar absorbing performance of corrugated structure. (1st December 2020) - Huang, Haoming; Wang, Wen; Cao, Taishan; Kuang, Jiacai; Deng, Yingjun; Hua, Manyu; Xie, Wei
Abstract: In this research, corrugated structure is invented as a radar absorbing structure and the effects of various factors on its radar absorbing performance are investigated. The results demonstrated that, the geometric parameters and the sheet resistance of the corrugated structure have significant influences on the reflection loss peaks and absorption bandwidth. Computational and experimental results confirm that the corrugated structure with conductive coating can improve the absorbing bandwidth and absorbing intensity. The designed corrugated structure has more than 90% absorption over a broad bandwidth of 2.31–18 GHz. The proposed longitudinal corrugated structure without panels improves the impedance matching between the surface of corrugated structure and the air. Thus, most incident radar wave is trapped into corrugated structure, resulting in the enhancement of absorption bandwidth. This structure has great potentials in antiradar detection technology and electromagnetic interference shielding.